2021
DOI: 10.3390/ani11082167
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Regulatory Roles of Herbal Extracts on the Growth, Immune System, and Reproduction of Fish

Abstract: The crucial need for safe and healthy aquatic animals obligates researchers in aquaculture to investigate alternative and beneficial additives. Medicinal herbals and their extracts are compromised with diverse effects on the performances of aquatic animals. These compounds can affect growth performance and stimulate the immune system when used in fish diet. In addition, the use of medicinal herbs and their extracts can reduce oxidative stress induced by several stressors during fish culture. Correspondingly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(39 citation statements)
references
References 111 publications
0
26
0
Order By: Relevance
“…Immunostimulants such as herbal extracts are considered as the potential alternative to antibiotics in aquatic species (Hoseinifar et al, 2020;Vaseeharan & Thaya, 2014). It has been revealed that herbal extracts not only enhance the immune system, but also induce digestive enzymes activity and increase the growth rate (Ahmadifar et al, 2021;Raissy et al, 2022) In the present study, dietary acorn extract affected growth, survival, haemolymph biochemistry, and proximate composition of P. leptodactylus.…”
Section: Discussionmentioning
confidence: 59%
“…Immunostimulants such as herbal extracts are considered as the potential alternative to antibiotics in aquatic species (Hoseinifar et al, 2020;Vaseeharan & Thaya, 2014). It has been revealed that herbal extracts not only enhance the immune system, but also induce digestive enzymes activity and increase the growth rate (Ahmadifar et al, 2021;Raissy et al, 2022) In the present study, dietary acorn extract affected growth, survival, haemolymph biochemistry, and proximate composition of P. leptodactylus.…”
Section: Discussionmentioning
confidence: 59%
“…The enhanced growth performance in beluga-fed dietary caffeic acid can also be related to the upregulated growth-related genes (Ahmadifar, Fallah, et al, 2021). The release of GH is involved in several metabolic functions, including protein synthesis, cellular RNA formation, and amino acids uptake (Triantaphyllopoulos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols can also show high potential as immunomodulators by activating immune-related genes, cytokines, antibodies, and metabolites (Ahmadifar, Fallah, et al, 2021). Consequently, high resistance to infection and farming stressors results from polyphenols supplementation (Alagawany et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals from medicinal plants have been found to modulate the expression of several genes in fish, which has been reviewed recently by Ahmadifar et al (48). IL-1β is a pro-inflammatory gene released from white blood cells (WBCs), attracting other WBCs and initiating an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%